The effect of aqueous and ethanolic extract of Iranian propolis on Candida Albicans isolated from the mouth of patients with colorectal malignancy undergone chemotherapy: An in-vitro study - Fatemeh Sayyadi; Saeed Mahdavi; Ali Akbar Moghadmnia; Dariush Moslemi; Atena Shirzad; Mina Motallebnejad (Babol University of Medical Sciences, 2020)
Background: Candidiasis is one of the most common fungal infections in immunosuppressed patients. The condition is usually treated with local and systemic antifungal agents. Given the antifungal properties of propolis, it appears this natural resin material can be effective in treating this infection. The aim of the present in vitro study was to compare the effect of Iranian propolis with those of routine antifungal agents on Candida species isolated from the oral candida lesions of patients with cancer, who had undergone chemotherapy, and a standard strain of Candida albicans. Methods: A total of 23 samples were collected from the oral cavities of patients with colorectal cancer, who had undergone chemotherapy with 5-fu. The fungal species were determined based on the results of culture in C. albicans chromagar medium, formation of the germ tube and formation of vesicles. The MIC of aqueous extract propolis (AEP) and ethanolic extract of propolis (EEP) and amphotericin B (AMP-B), fluconazole (FL) and nystatin (NYS) were compared. Results: A total of 23 oral C. albicans samples were isolated. The MICs of FL and AMP- B were similar and less than those of EEP, AEP and NYS (P<0.001). In addition, the MIC of AEP was higher than EEP (P<0.001). The MIC of AMP- B on the strains isolated from the patients was more than that of the standard strain (P=0.012). Conclusion: The aqueous and ethanolic extracts of Iranian propolis exhibited antifungal activity, with a greater effect of the EEP compared to the AEP.